Efektivitas Aplikasi “Sayang Warga” dalam Meningkatkan Pelayanan Pendataan Warga oleh Kader Surabaya Hebat (KSH) di Kelurahan Sememi Kota Surabaya - Grescia Alfita Miryana; Eva Hany Fanida (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The implementation of e-government is an important step in public service innovation. The Surabaya City Government created the Sayang Warga (ASW) Application as a solution to the development of public service technology. This type of research uses descriptive qualitative research. This study measures the effectiveness of digital-based public services according to Pedrosa et al. (2020). The results of the study showed that ASW was considered effective in relation to citizen data collection services carried out by the Great Surabaya Cadres in Sememi Village, Surabaya City. In terms of ease of use, ASW makes it easier to record and report citizen problems in real time. Useful, this application provides benefits in accelerating the work of cadres. Simple, user-friendly application design makes it easier to record citizen data. Trustworthy, the application has good security measures. Available, this application faces technical obstacles such as internet disruptions that affect work efficiency. Understandably, the application design is easy to understand, but the survey menu is quite confusing. Consistent, this application maintains a simple design. Fast, this application supports fast and efficient data collection, even though there is overlapping of village employee duties.